New exact solutions for the Kaup-Kupershmidt equation - İnç, Mustafa; Miah, Mamun; Chowdhury, Akher; Ali, Shahadat; Rezazadeh, Hadi; Akinlar, Mehmet Ali; Chu, Yu-Ming (Amer Inst Mathematical Sciences-Aims, 2020)
We present new exact solutions for the (1+1)-dimensional Kaup-Kupershmidt (KK) equation by employing method of double (G'/G, 1/G)-expansion. We express solutions by hyperbolic, trigonometric and rational functions explicitly. Computational results indicate the efficiency and applicability potential of the method.
Keywords: Kaup-Kupershmidt equation; the method of double (G '/G, 1/G)-expansion; exact solutions